2017
DOI: 10.1111/jphp.12796
|View full text |Cite
|
Sign up to set email alerts
|

β-2-himachalen-6-ol protects against skin cancer development in vitro and in vivo

Abstract: In conclusion, HC treatment induced cell cycle arrest (low dose) and promoted apoptosis partly via inhibition of the MAPK/ERK and PI3K/AKT pathways with no significant toxicity to laboratory mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
(123 reference statements)
2
10
0
Order By: Relevance
“…Moreover, it has been reported that the antitumor activity of these compounds was associated with the induction of apoptosis through caspase-3 activation and the inhibition of DNA. [15][16][17][18] Meanwhile, the literature survey revealed that semicarbazone and thiosemicarbazone derivatives have demonstrated great promise in pharmacological and industrial chemistry. [19] Also, they have been widely used as useful intermediates to produce heterocyclic compounds (such as thiazoles and 4-thiazolidinones) and as ligands in metal-complexes synthesis because of their excellent chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that the antitumor activity of these compounds was associated with the induction of apoptosis through caspase-3 activation and the inhibition of DNA. [15][16][17][18] Meanwhile, the literature survey revealed that semicarbazone and thiosemicarbazone derivatives have demonstrated great promise in pharmacological and industrial chemistry. [19] Also, they have been widely used as useful intermediates to produce heterocyclic compounds (such as thiazoles and 4-thiazolidinones) and as ligands in metal-complexes synthesis because of their excellent chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, earlier work in our lab showed that β-2-himachalene-6-ol, an isomer of 7-HC, isolated from wild carrot demonstrated potent anticancer activity against several human and murine cancer cell lines 22,23 . β-2-Himachalene-6-ol was also found to exhibit significant anti-tumor promoting effect against DMBA/TPA skin carcinogenesis and dimethylhydrazine-induced colon carcinogenesis in mice 24 .…”
Section: Discussionmentioning
confidence: 96%
“…More recently, β‐2‐himachalen‐6‐ol ((Figure 1): A‐1) and 2‐himachelen‐7‐ol ((Figure 1): A‐2) showed promising cytotoxic activity against B16‐F‐10, Caco‐2, MB‐MDA‐231 and A‐549 cells. In the same way, the mechanism of action study showed that these products induced apoptosis through the activation of caspase‐3 in renal cell carcinoma (HaCaT‐ras) ((Figure 1): A‐1) or ((Figure 1): A‐2), associated with the ability to interact with DNA [6–8] …”
Section: Introductionmentioning
confidence: 87%
“…In the same way, the mechanism of action study showed that these products induced apoptosis through the activation of caspase-3 in renal cell carcinoma (HaCaT-ras) ((Figure 1): A-1) or ((Figure 1): A-2), associated with the ability to interact with DNA. [6][7][8] Nowadays, heterocyclic compounds carrying oxygen and nitrogen are an important class of compounds with interesting biological and pharmacological activities, due to their similarity with various bioactive molecules of natural origin. [9][10][11] Among these compounds, substituted thiazolidin-4-ones mediated significant antiproliferative effects, studies concerning structure-activity relationships have shown that the cytotoxic potency of compounds was highly dependent on the types and patterns of N-substitution on the thiazolidin-4-one ring.…”
Section: Introductionmentioning
confidence: 99%